ANALISIS KEBUTUHAN TENAGA KEPERAWATAN MENGGUNAKAN METODE WORKLOAD INDICATOR STAFF NEED (WISN) DI PELAYANAN RAWAT INAP TERATAI PENYAKIT DALAM RUMAH SAKIT UMUM PUSAT FATMAWATI - Alfadha Henryan Fenyara, (2022)
The level of patient satisfaction is one of the standards for measuring the success of hospitals in providing effective and efficient services. The availability of human resources is one of the requirements to improve services that are effective and efficient. Based on data in the Fatmawati Hospital strategic plan report for 2020-2024, there was a decrease in satisfaction which should have been from 81.4% in 2017 to 79.1% in 2019. One of the reasons for the decline was due was less than optimal services due to excessive workload. The purpose of this study was to determine the number of nurses needed by analyzing the actual workload of nurses. The research method used a qualitative approach with descriptive techniques. Data collection techniques are interviews and observations. One informant from the head of the ward was interviewed and three nurses were interviewed and observed. Data analysis techniques with reduction and presentation of data and drawing conclusions. The results of the study found that productive activities were 84% while the standard was 80%. This means that there is a gap of 4% and it is recommended to increase the number of nurses. In addition, it is supported based on the overall calculation of the employee needs indicator method. The number of employees should be 32 people, while in the current condition there are 21 people, there is a shortage of 11 people with a WISN ratio of 0.66.